STUDI KINERJA KOPERASI SERBA USAHA (KSU) SUMBER REJEKI DI DESA KARYA BHAKTI KECAMATAN MUARA WAHAU KABUPATEN KUTAI TIMUR (The Performance Study of Multipurpose Business Cooperative (MBC) of Sumber Rejeki in Karya Bhakti Village Muara Wahau Subdistrict East Kutai District) - FIRDA JUITA; RISKA YULIAWATI (Universitas Mulawarman (University of Mulawarman), 2018)
This study aimed to determine the performance of Multipurpose Business Cooperatives of Sumber Rejeki according to the perception of cooperative management and member. Determination of respondents was by simple random sampling. The number of respondents was 42 respondents. Samples consisted 9 members of board and 33 members who are still active. Data were collected by direct observation and interviews with respondents. Data were analyzed using the Likert scale. Based on the results of the study, the performance of Multipurpose Business-Cooperative of Sumber Rejeki in Karya Bhakti Village, Muara Wahau Subdistrict, East Kutai District, based on the perception of board was in the good category with a total score of 313 with an average of 34.78. Performance of Multipurpose Business Cooperative of Sumber Rejeki in Karya Bhakti Village, Muara Wahau District based on the perception of members are in the good category with a total score of 1,290 with an average of 39.09. So as a whole performance Cooperative of Sumber Rejeki in the Village of Karya Bhakti belonging to the category of good.